Arterial baroreflex control of muscle sympathetic nerve activity under orthostatic stress in humans - Ichinose, Masashi; Nishiyasu, Takeshi (Frontiers in Physiology, 2012)
The mechanisms by which blood pressure is maintained against the orthostatic stress caused by gravity’s effect on the fluid distribution within the body are important issues in physiology, especially in humans who usually adopt an upright posture. Peripheral vasoconstriction and increased heart rate are major cardiovascular adjustments to orthostatic stress and comprise part of the reflex response elicited via the carotid sinus and aortic baroreceptors (arterial baroreflex: ABR) and cardiopulmonary stretch receptors (cardiopulmonary baroreflex). In a series of studies, we have been characterizing the ABR-mediated regulation of cardiovascular hemodynamics and muscle sympathetic nerve activity (MSNA) while applying orthostatic stress in humans. We have found that under orthostatic stress, dynamic carotid baroreflex responses are modulated as exemplified by the increases in the MSNA, blood pressure and heart rate responses elicited by carotid baroreflex unloading and the shorter period of MSNA suppression, comparable reduction and faster recovery of MAP and greater heart rate response to carotid baroreflex stimulation. Our results also show that ABR-mediated beat-to-beat control over burst incidence, burst strength and total MSNA is progressively modulated as orthostatic stress is increased until induction of syncope, and that the sensitivity of ABR control over the aforementioned MSNA variables is substantially reduced during the development of syncope. We suggest that in humans, the modulation of ABR function under orthostatic stress may be one of the mechanisms by which blood pressure is maintained and orthostatic hypotension limited, and impairment of ABR control over sympathetic vasomotor activity leads to the severe hypotension associated with orthostatic syncope.